Investigating teaching strategies that ensure the inclusivity of learners with physical and/ or mental impairments in Lesotho - Mateusi, Maphaphi Clement (Bloemfontein : Central University of Technology, Free State, 2011)
The purpose of this study is to investigate teaching strategies that ensure the inclusivity of learners with physical and/or mental impairments in the mainstream schools in Lesotho. The intention being to equip educators with strategies that can be employed in order to address this didactical challenge at mainstream schools. The inclusion of impaired learners can be achieved only if teachers understand the purpose of inclusive education as defined by Van Rooyen and De Beer (2006) that inclusive education is an education system that ensures that all children learn and participate regardless of their disabilities. The study followed a mixed method approach, in the form of a survey, that is semi-structured questionnaire for teacher respondents while an observation coupled with informal discussion was utilized for the learner respondents. Population and sampling consisted of 211 teachers randomly drawn from 23 primary schools found in Berea and Maseru districts of Lesotho. The completed questionnaires were collected and analysed. The study found that there are challenges experienced by physically and/or mentally impaired learners with their teachers and peers. According to the findings of the research, Lesotho teachers in mainstream classes do not have enough training to work with impaired learners. Given this situation, it is not only recommended that the current group of teachers are re-skilled and re-trained through short courses and workshops, but also that teacher training colleges and university in Lesotho are encouraged to constantly review and update their programmes so that they are responsive to the professional needs of educators. Appropriate inclusive teaching strategies are also recommended to assist in addressing this challenge. Educators should be sufficiently supported by the para-professionals in order to make inclusive education successful. Government experts should work collaboratively with the Lesotho College of Education and the National University of Lesotho with regard to the attainment of these skills and competencies, in order to improve the work of the educators at schools. At school level, special educators should be hired in order to identify learners with impairments.
Thesis ( M. Ed.(Educational Management)) - Central University of technology, Free State, 2011
Keywords: Central University of Technology, Free State - Dissertations; Inclusive education - Lesotho; Children with disabilities - Education - Lesotho; Mainstreaming in education; Effective teaching; Dissertations, academic - South Africa - Bloemfontein